Sparkling wines' future in the USA: insights from the industry. (20th October 2021) - Vecchio, Riccardo; Gergaud, Olivier; Pomarici, Eugenio
The current study analyses the growth potential of four different sparkling wines (California sparkling, Cava, Champagne and Prosecco) in the US market based on the views and judgment of a large sample of 843 trade actors. Findings of an online survey suggest that sparkling wines coming from Italy (Prosecco), Spain (Cava) and California have higher growth potentials than wines produced in the Champagne region of France. This is in line with the fact that Champagne wines are sold at very high prices internationally for historical reasons (monopoly power, first-mover advantage, well-established large brands). Furthermore, results suggest that a good price/quality ratio, positive wine critics, the fact that new consumers are choosing this wine are associated with higher estimated growth potentials by traders. Managerial implications for small and medium businesses are presented and critically discussed. We also analyse our results in the light of the new legislation on US imports that was adopted in October 2019 and that will hit Cava wines only.